2010
DOI: 10.1002/ana.22230
|View full text |Cite
|
Sign up to set email alerts
|

A Gradient of neuronal loss and meningeal inflammation in multiple sclerosis

Abstract: We demonstrate substantial cortical neurodegeneration and generalized cell loss in progressive MS in association with meningeal inflammation and lymphoid tissue formation, supporting the hypothesis that cytotoxic factors diffusing from the meningeal compartment contribute to grey matter pathology and the consequent increase in clinical disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

64
776
5
14

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 651 publications
(859 citation statements)
references
References 45 publications
64
776
5
14
Order By: Relevance
“…However, similar to human AD patients immunized with Ab (Elan's trial), the immunized mice develop meningoencephalitis presumably due to T cell activation at the perivascular/subarachnoid space prior to crossing the glia limitans. Similar effects of T cell activation at the brain vasculature were also described in MS (14) and are likely to impair the brain-endogenous capacity for cell renewal and repair (48,49). In contrast, because activated T cells in the current study were injected directly into the lateral ventricle, no further activation was required prior to crossing the epithelial layer or the vasculature's glia limitans into the brain parenchyma, and, as such, the injected cells induced neither significant vascular pathology nor cellular apoptosis, but instead, similar to previous studies demonstrating the positive effects of T cells and IFN-g on neurogenesis (24, 27, 50, 51), slightly enhanced hippocampal neurogenesis in an age-dependent manner.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, similar to human AD patients immunized with Ab (Elan's trial), the immunized mice develop meningoencephalitis presumably due to T cell activation at the perivascular/subarachnoid space prior to crossing the glia limitans. Similar effects of T cell activation at the brain vasculature were also described in MS (14) and are likely to impair the brain-endogenous capacity for cell renewal and repair (48,49). In contrast, because activated T cells in the current study were injected directly into the lateral ventricle, no further activation was required prior to crossing the epithelial layer or the vasculature's glia limitans into the brain parenchyma, and, as such, the injected cells induced neither significant vascular pathology nor cellular apoptosis, but instead, similar to previous studies demonstrating the positive effects of T cells and IFN-g on neurogenesis (24, 27, 50, 51), slightly enhanced hippocampal neurogenesis in an age-dependent manner.…”
Section: Discussionsupporting
confidence: 60%
“…However, although it is believed to underlie the pathogenesis of MS (13)(14)(15)(16), in other neurodegenerative processes including brain injury (17,18), amyotrophic lateral sclerosis (19), stroke (20), and Alzheimer's disease (AD), T cell infiltration into the CNS has been implicated either as exacerbating neurodegeneration (21)(22)(23) or, in other instances, as beneficial. Regulatory cytokine profiles of certain T cell subsets (24)(25)(26) or the ability of T cells to secrete neurotrophic factors (27,28) have been suggested as mechanisms underlying the beneficial effects of T cell infiltration into the CNS.…”
mentioning
confidence: 99%
“…For example, several recent studies of grey and white matter demyelination in different regions of the CNS found that the extent of cortical demyelination is greater than that found in white matter 34 and that, although cortical demyelination sometimes occurred together with demyelination in the adjacent white matter (leukocortical lesions), in most instances, the cortex was affected independently from white matter lesions 35,36 . Another study observed a gradient of neuronal loss in the precentral gyrus of MS cases that exhibited extensive subpial demyelination with the greatest loss in the outer cortical layers 17 . There was no relationship between this gradient and the white matter lesion volume or location, which argues strongly against an influence of white matter lesions on grey matter subpial pathology.…”
Section: Evidence For Independent Grey Matter Damagementioning
confidence: 96%
“…In post mortem samples taken from individuals in the advanced stages of multiple sclerosis, high numbers of immune cells were only detected in Type I grey matter lesions ( Figure 1A): all other grey matter lesions were categorized as relatively "noninflammatory" [11][12][13] . Moreover, according to post-mortem studies, neuronal loss occurs within both grey matter demyelinated lesions and normal appearing grey matter 12,16,17 , suggesting that neuronal loss might occur independently from grey matter demyelination.…”
Section: Are White and Grey Matter Damage Linked?mentioning
confidence: 99%
See 1 more Smart Citation